Risk-adapted Treatment for Severe B-Lineage Posttransplant Lymphoproliferative Disease After Solid Organ Transplantation in Children. Issue 2 (February 2016) - Giraldi, Eugenia; Provenzi, Massimo; Conter, Valentino; Colledan, Michele; Bolognini, Stefania; Foglia, Carlo; Sebastiani, Roberta; Fiocchi, Roberto; Gianatti, Andrea; D'Antiga, Lorenzo; Rambaldi, Alessandro
Abstract : Background: Optimal management of posttransplant lymphoproliferative disease (PTLD) remains to be defined due to heterogeneity of this condition and lack of predictors of the outcome. Here we report our experience with pediatric PTLD nonresponsive to immunosuppression (IS) withdrawal, managed after stratification into high and low risk according to the presenting features. Methods: This is a single-center retrospective review of prospectively enrolled patients. From 2001 to 2011, 17 children were diagnosed with severe B-lineage, CD20+, PTLD after a median of 37 months (range, 5–93) from liver (12), heart (4), or multiorgan (1) transplantation. Treatment was tailored on 2 risk groups: (1) standard-risk (SR) patients received IS reduction and rituximab; (2) high-risk (HR) patients received IS discontinuation, rituximab and polychemotherapy. Results: The cumulative incidence of rejection at 1 and 5 years after the diagnosis of PTLD was 35% (95% confidence interval [95% CI], 18-69%) and 53% (33-85%), respectively, whereas the disease-free survival at 1 and 5 years was 94% (95% CI, 65-99%) and 75% (45-90%), respectively. Three children died, PTLD-free, from different transplant-related complications: primary nonfunction after retransplantation (liver), cytomegalovirus disease 21 months after PTLD treatment (liver), graft dysfunction 25 months after PTLD (heart). Conclusions: Severe B-lineage PTLD after solid organ transplantation may be classified as SR or HR and treated accordingly with a tailored protocol obtaining a satisfactory long-term outcome. This approach accomplishes the control of lymphoproliferation in severe forms as well as the minimization of toxicity in milder PTLDs.